1998
DOI: 10.1016/s0375-9474(98)00117-1
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron photo-disintegration with polarised photons in the energy range 30–50 MeV

Abstract: The reaction d( γ, np) has been studied using the tagged and polarised LADON gamma ray beam at an energy 30 − 50 M eV to investigate the existence of narrow dibaryonic resonances recently suggested from the experimental measurements in a different laboratory. The beam was obtained by Compton back-scattering of laser light on the electrons of the storage ring ADONE. Photo-neutron yields were measured at five neutron angle ϑ c.m.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Let us make some remarks on current conservation. The Mandelstam vertex consists of one-and two-body parts, Λ µ (p, k; P, K) = Λ [1] µ (p, k; P, K) + Λ [2] µ (p, k; P, K). The second part of the Mandelstam vertex determines two-body contributions of the conserved EM current.…”
Section: Deuteron Photodisintegration Cross Sectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Let us make some remarks on current conservation. The Mandelstam vertex consists of one-and two-body parts, Λ µ (p, k; P, K) = Λ [1] µ (p, k; P, K) + Λ [2] µ (p, k; P, K). The second part of the Mandelstam vertex determines two-body contributions of the conserved EM current.…”
Section: Deuteron Photodisintegration Cross Sectionmentioning
confidence: 99%
“…[36] it was shown that the gauge independence condition for the elastic electrondeuteron scattering amplitude is fulfilled in the impulse approximation for many-rank separable BS kernels, implying that q · M [2] f i = 0. In case of the deuteron breakup in the final 2N state isospin I = 1 states are present, yielding a nonvanishing isovector contribution, q · M [2] f i = 0. Consequently the two-body Mandelstam current operator should be added to guarantee the gauge independence.…”
Section: Deuteron Photodisintegration Cross Sectionmentioning
confidence: 99%
See 3 more Smart Citations